Globalization Versus Segregation - Business Cycles Synchronization in Europe - Sebastian Florian Enea; Silvia Palac\~a (CES Working Papers, 2012)
Globalization and business cycles are equally elusive economic phenomena; hence they represent a continuous research possibility and a source of possible inquiries due to their complex nature. The aim of the paper is to explain the synchronization of business cycles using the relationship between the growth rate of the GDP and FDI, considered as percentage of the GDP. The results show that there is no unique European business cycle, but two cores between which countries migrate and stress out the importance of the FDI channel in business cycle transmission. The future research d irections will employ fuzzy cluster techniques, used on a larger sample.
Keywords: E32; E37; F21; F44; 330; real convergence; financial convergence; economic and financial crises; EMU Romania